Widespread Moulin Formation During Supraglacial Lake Drainages in Greenland. Issue 2 (17th January 2018) - Hoffman, Matthew J.; Perego, Mauro; Andrews, Lauren C.; Price, Stephen F.; Neumann, Thomas A.; Johnson, Jesse V.; Catania, Ginny; Lüthi, Martin P.
Abstract: Moulins permit access of surface meltwater to the glacier bed, causing basal lubrication and ice speedup in the ablation zone of western Greenland during summer. Despite the substantial impact of moulins on ice dynamics, the conditions under which they form are poorly understood. We assimilate a time series of ice surface velocity from a network of eleven Global Positioning System receivers into an ice sheet model to estimate ice sheet stresses during winter, spring, and summer in a ∼30 × 10 km region. Surface‐parallel von Mises stress increases slightly during spring speedup and early summer, sufficient to allow formation of 16% of moulins mapped in the study area. In contrast, 63% of moulins experience stresses over the tensile strength of ice during a short (hours) supraglacial lake drainage event. Lake drainages appear to control moulin density, which is itself a control on subglacial drainage efficiency and summer ice velocities. Plain Language Summary: Moulins are the conduits that allow water melting on the surface of the Greenland Ice Sheet to drain to its base and cause the ice to flow faster. Forming a moulin in Greenland requires a crack on the surface that becomes filled with enough water to drive the crack all the way through the ice. However, a large fraction of moulins in Greenland form away from the ice sheet's crevasse fields, making their formation a mystery. We forced a model of ice sheet flow to match measurements of the ice speed measured by GPS every 2 h. At most of the moulin locations in the area studied, the stresses predicted by the model were too small to fracture the ice and allow moulins to form during winter, spring, and most of summer. However, fracturing did occur at most moulin locations when large lakes on the surface of the ice drained catastrophically to the bed over a few hours. These rare and brief lake drainages must be the cause of most of the moulins, and they therefore have a lasting impact on the flow of water into the ice sheet and the changes in the flow of the ice this causes. Key Points: Ice sheet model inversion using ice velocity from 11 station GPS network reveals Greenland ice sheet surface stresses at hourly resolution Conditions for fracturing and moulin formation expand slightly in spring and summer but substantially during brief lake drainage event Most mapped moulins could form only during large ice stresses associated with supraglacial lake drainages